Depistage Des Lesions Du Col Uterin Au Chu Tokoin De Lome : Resultats D’une Serie De 512 Cas. - Darre, Tchin; Aboubakari, Abdoul-Samadou; James, Yaovi Edem; Folligan, Koué; N’bortche, Bingo; Amegbor, Koffi; Akpadza, Koffi; Napo-Koura, Gado (European Scientific Journal, ESJ, 2016)
Purpose: Cervical cancer remains a real public health problem in Togo. This study was undertaken to sensitize women and to determine the prevalence of precancerous and canrous lesions of the cervix in the Togolese woman. Material and methods: This is a retrospective descriptive study of the results of a consecutive series of Pap smears performed in the Laboratory of Pathological Anatomy and Cytology CHU Tokoin Lome 2011-2013. Results: Epidemiological, 512 FCV were interpretable. The average age of women was 37.6 years, extreme 19 and 87 years. By occupation, we noted a predominance of unemployed women (351cas, 68,6%), followed by women traders (103 cases, 20,1%) . The distribution by marital status was possible to observe a predominance of married women (234 cases, 45, 7 %). In terms of reproductive history, we found a mean gravidity and parity respectively 3, 5 and 2. We noted 22 women living with HIV, 77.2% were infected with HIV1. Cytopathological, 512 smears selected, we observed 44 abnormal smears (8,6%). It was indeterminate lesions ASCUS / ASCUS (8 cases), endocervical hyperplasia (3 cases), low-grade lesions (17 cases), high-grade lesions (10 cases) and invasive carcinoma (6 cases). Conclusion: The detection rate of cervical cancer is low among the Togolese woman. The health professionals should take the habit of asking the FCV any woman having a consultation.